A new species of Valeriana from the Andean region of northwestern Argentina, based on morphological and molecular data - Acosta, Juan Manuel (2015)
Valeriana serratifolia, a new species from the Andean region of northwestern Argentina, is described and illustrated. It can be distinguished from its closest morphological taxon, V. macrorhiza, by its entire, spathulate leaves with serrulate margin, and falcate fruits, 2–2.5 mm long, crowned by the reduced annular calyx shifted toward the ventral face. A phylogenetic analysis based on DNA sequences of plastid markers trnL-F and trnK intron supported V. macrorhiza as its closest related species. We also provide a key to differentiate V. serratifolia from the epappose species of Valeriana from Argentina.